Sea of faith : Islam and Christianity in the medieval Mediterranean world - O'Shea, Stephen, (Walker : Distributed to the trade by Holtzbrinck Publishers, 2006)
The shared history of Christianity and Islam began, shortly after Islam emerged in the seventh century A.D., with a question: Who would inherit the world of the Mediterranean? Sprung from the same Abrahamic source, the two faiths played out what historian O'Shea calls "sibling rivalry writ very large." Their clashes on the battlefield were balanced by long periods of coexistence and mutual enrichment, and by the end of the sixteenth century the religious boundaries of the modern world were drawn. O'Shea chronicles the meetings of minds and the collisions of armies that marked the Middle Ages--the better to understand their apparently intractable conflict today. For all the great and everlasting moments of cultural interchange and tolerance--in Cordoba, Palermo, Constantinople--the ultimate "geography of belief" was decided on the battlefield. O'Shea recounts seven pivotal battles between the forces of Christianity and Islam that shaped the Mediterranean world.--From publisher description.